MITOS LARANGAN MENIKAH 2 SAUDARA KANDUNG LAKI-LAKI DAN PEREMPUAN DALAM KURUN WAKTU SATU TAHUN DIDESA PAKUAN RATU WAYKANAN - Sari, Maya (Program Studi Pendidikan Bahasa Lampung, FKIP Universitas Lampung, 2023)
Abstract This article reveals how two Arabic consonant sounds: the glottal stop and the pharyngeal sis are pronounced by native speakers of the Lampung language when reciting Surah Al-Fatihah. The theory used in this research is articulatory phonetics. Using this theory, each sound is described and analyzed according to place, way of articulation and sound. Data in the form of sound recordings from speakers of the Arabic language of the Al-Qur’an and speakers of the Lampung language were transcribed using the International Phonetic Alphabet (AFI), and described based on place, method of articulation and sound. To see the visualization of the sound, researchers used tools in the form of a computer program, Praat. Using the contrastive analysis method, researchers analyzed the differences in the features of the two sounds. The results of the research show that there are 6 pronunciations of glottal consonant sounds and 6 pronunciations of pharyngeal consonant sounds in Surah Al-Fatihah. These two consonant sounds are each pronounced as a vowel sound by native Lampung speakers. This research concludes that there is a change in the sound of the Arabic language of the Koran in the pronunciation of Surah Al-Fatihah by native Lampung speakers. Abstrak Dalam Islam pernikahan adalah salah satu hal yang dianjurkan oleh Rasullullah. Ada beberapa hal yang harus diperhatikan dalam pernikahan yakni: syarat, rukun dan larangan pernikahan. Namun telah terjadi di suatu kampung yang melarang menikah 2 saudara kandung laki-laki dan perempuan dalam kurun waktu satu tahun didesa pakuan ratu waykanan hal ini disebabkan oleh faktor yang terjadi di masyarakat diakibatkan karna kampung Pakuan Ratu memiliki bukti yang telah terjadi dikampung tersebut. Jika dilakukan maka akan terjadi malapetaka jika mereka tetap melangsungkan pernikahan dan dalam hal ini maka akan terjadi suatu akibat yang ditimbulkan antara kedua belah pihak yakni: Mandul, gila, sakit-sakitan, hilang bahkan akan sampai meninggal dunia. Dan semenjak adanya faktor tersebut maka masyarakat yang berada di Pakuan Ratu melarang putra-putri mereka untuk menikah secara bersamaan dalam satu tahun, dan justru mereka lebih merelakan anak gadis mereka untuk tidak menikah dari pada harus menikah secara bersamaan. Sehingga dari latar belakang yang ada maka penulis melakukan penelitian.